EFEK KOMPENSASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. PLN (Persero) UNIT INDUK WILAYAH SULSELRABAR - Mappamiring Mappamiring (Pascasarjana Universitas Halu Oleo, 2020)
This research was conducted with the following objectives: (1) To analyze the effect of compensation on employee productivity, (2) to analyze the effect of work discipline on employee productivity, (3) to analyze the effect of compensation and work discipline on employee productivity of PT. PLN (Persero) Sulselrabar Regional Main Unit. This study uses an explanatory research approach. The population of this study were all employees of PT. PLN (Persero) Sulselrabar Regional Main Unit as many as 135 permanent employees with a sampling technique using total sampling technique or saturated sample which is meant by total sampling here is that the researcher uses all the population as the sample. Data collection used questionnaires and interviews, while data analysis was performed using multiple linear regression analysis. The results of the study at the 5% significance level indicate that: 1) compensation for both financial and non-financial compensation has a significant positive effect on employee productivity, 2) The application of work discipline has a positive and significant effect on employee productivity, 3) compensation and discipline variables have a simultaneous effect on employee productivity. Productivity of employees of PT. PLN (Persero) Sulselrabar Regional Main Unit.